2017
DOI: 10.1038/s41598-017-13704-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotational dynamics and dynamical transition of water inside hydrophobic pores of carbon nanotubes

Abstract: Water in a nanoconfined geometry has attracted great interest from the viewpoint of not only basic science but also nanofluidic applications. Here, the rotational dynamics of water inside single-walled carbon nanotubes (SWCNTs) with mean diameters larger than ca. 1.4 nm were investigated systematically using 2H nuclear magnetic resonance spectroscopy with high-purity SWCNTs and molecular dynamics calculations. The results were compared with those for hydrophilic pores. It was found that faster water dynamics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…4B and table S2). The QENS data for τ R agree well with data from nuclear magnetic resonance (NMR) measurements and molecular dynamics simulation results for nanoconfined water in other systems ( 11 , 14 , 24 29 ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…4B and table S2). The QENS data for τ R agree well with data from nuclear magnetic resonance (NMR) measurements and molecular dynamics simulation results for nanoconfined water in other systems ( 11 , 14 , 24 29 ).…”
Section: Resultssupporting
confidence: 75%
“…( B ) Relaxation times (τ R = ħ/ Γ R ) from analysis of the Q -independent broad QENS component for PTI·H 2 O between 345 to 150 K ( Fig. 3C ) compared with water contained within larger-diameter (1.7 nm) CNTs (light brown) ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly intriguing are its transport properties under the confinement of nanopores or nanochannels, which are unlike those of other common molecules, and where it displays unexpectedly high transport rates, far exceeding those predicted by conventional hydrodynamics. These have major influence in diverse applications, such as desalination, gas and ion separation, and natural processes such as transport in biological channels, as well as a host of others. The fast diffusive transport of water under molecular level confinement in carbon nanotubes (in particular at the sub-nanometer level) has received much interest in the literature, and although most studies have centered on the self-diffusivity of water and its anomalous behavior at various diameters, in actual applications, it is the collective transport of water molecules across these nanoscopic channels that is important. For example, collective diffusion is central to exploiting the anomalies of the water transport in applications such as water desalination or understanding the mechanism of fast transport of water in biological channels like aquaporin.…”
Section: Introductionmentioning
confidence: 99%
“…14 Molecular dynamics simulations by Kalra et al 15 demonstrate nearly frictionless flow of water molecules inside narrow CNTs under an osmotic gradient. Nuclear magnetic resonance (NMR) measurements and MD simulations by Kyakuno et al 16 suggest that faster transport of water inside CNTs can be achieved by increasing the hydrophobicity of the pore walls and by reducing the diameters. Liu et al 17 have found through pulse field gradient NMR experiments that the diffusivity of water in narrow double-walled CNTs is greater than that in multiwalled CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Its numerous physical, chemical and thermodynamic properties stimulated many studies in the past decades [1,2]. To unravel the complex behavior of water, single molecule rotational spectroscopies have drawn considerable attention [3][4][5][6][7][8]. An intriguing aspect of water dynamics is the distinct rotational quantum behavior of its ortho (𝐼 = 1) and para (𝐼 = 0) spin isomers.…”
mentioning
confidence: 99%